Forefoot Injuries in Athletes: Integration of the Movement System - Lindsay A Carroll; Stephen Paulseth; RobRoy L Martin (International Journal of Sports Physical Therapy)
Despite the prevalence of forefoot related problems in athletes, there are few comprehensive summaries on examination and intervention strategies for those with forefoot related symptoms. While many factors may contribute to pathology and injury, the presence of abnormal foot alignment can negatively affect lower extremity biomechanics and be associated with injuries. Physical therapists may use the characteristics associated abnormal pronation or abnormal supination to describe the movement system disorder and serve as a guide for evaluating and managing athletes with forefoot pathologies. Athletes with an abnormal pronation movement system diagnosis typically demonstrate foot hypermobility, have decreased strength of the tibialis posterior muscle, and present with a medially rotated lower extremity position. Athletes with abnormal supination movement system diagnosis typically demonstrate foot hypomobility, decreased strength of the fibularis muscles, and a laterally rotated lower extremity position. Interventions of manual therapy, taping, strengthening exercises, and neuromuscular reeducation can be directed at the identified impairments and abnormal movements. The purpose of this clinical commentary is to integrate a movement system approach in pathoanatomical, evaluation, and intervention considerations for athletes with common forefoot pathologies, including stress fractures, metatarsalgia, neuroma, turf toe, and sesamoiditis. By applying a prioritized, objective problem list and movement system diagnosis, emphasis is shifted from a pathoanatomical diagnosis-based treatment plan to a more impairment and movement focused treatment.